De estatura regular Height and Filipino Bodily Representations during the Spanish Colonial Period (1521–1898) - Lasco, Gideon (Philippine Studies: Historical and Ethnographic Viewpoints, 2020)
This article seeks to contribute to the “history of height” in the Philippines by looking at Filipino bodily representations and height differences during the Spanish colonial period. From Pigafetta’s account onward, European chroniclers typically described Indios (natives) as having average, varied, or unremarkable height. However, during the nineteenth century a new discourse emerged: that of a short-statured Filipino. Likely the consequence of actual physical changes and nascent racial ideologies on the part of Spaniards, this view would set the stage for Filipinos to be typologized as “short”—and for shortness to be problematized as a sign of racial and social inferiority.